2008
DOI: 10.1063/1.2905537
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity Discrepancy between RGB and RHB Stars of the Globular Cluster M15

Abstract: The surveys of Sneden et al. (1997Sneden et al. ( , 2000 found star-to-star abundance scatter of the light elements and the neutroncapture elements in M15 Red Giant Branch (RGB) stars. Further examination of three select RGB tip stars revealed a distinct r-process nucleosynthetic signature (consistent with a scaled solar system r-process abundance distribution). As part of a general survey of metal-poor red horizontal branch (RHB) stars, Preston et al. (2006) observed six RHB members of M15. They detected some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
136
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(145 citation statements)
references
References 6 publications
8
136
0
1
Order By: Relevance
“…The abundances of the s-process elements were derived using the technique of synthetic spectrum line profile fitting through the driver synth in MOOG (version 2017(version , Sneden 1973Sobeck et al 2011). We used 1D-LTE plane-parallel MARCS model atmospheres (Gustafsson et al 2008), fixing the atmospheric parameters to the values we found in Paper I, both for the cluster stars and the GBS.…”
Section: Abundance Measurementsmentioning
confidence: 99%
“…The abundances of the s-process elements were derived using the technique of synthetic spectrum line profile fitting through the driver synth in MOOG (version 2017(version , Sneden 1973Sobeck et al 2011). We used 1D-LTE plane-parallel MARCS model atmospheres (Gustafsson et al 2008), fixing the atmospheric parameters to the values we found in Paper I, both for the cluster stars and the GBS.…”
Section: Abundance Measurementsmentioning
confidence: 99%
“…9. In addition, our MOOG version does not include the effect of Rayleigh scattering (see, e.g., Sobeck et al 2011). This effect is increasingly important for blue absorption lines in metal-poor stars and would lead to slightly higher Sr abundances if properly treated.…”
Section: Strontiummentioning
confidence: 99%
“…For the analysis, we used the LTE code MOOG 2 (version 2017, Sneden 1973;Sobeck et al 2011 Barklem et al 2000 and references therein).…”
Section: Optical Analysismentioning
confidence: 99%